Computer related musculoskeletal ill-health among upper-secondary school pupils 2005 - Questionnaire to students - Palmerud, Gunnar; Wigaeus Tornqvist, Ewa; Toomingas, Allan; Mortimer, Monica; Hansson Risberg, Eva; Isaksson, Anita; Palm, Peter (Arbetslivsinstitutet, 2006)
The data collection was performed in high schools in the counties of Stockholm, Södermanland, Uppsala and Västmanland during the autumn of 2005.

The study consisted of two parts:
1. Questionnaires for the students.
2. Ergonomic evaluation of the schools computer workplaces and a short interview with the person responsible for the computers at the school.

An information letter was sent to the school leaders where the setup and implementation of the study were explained. After that the school leaders were contacted by telephone and asked if their school wished to participate in the study. If they chose to take part, they were asked to send a record of all students in the second grade to Working Life Institute (Arbetslivsinstitutet). From these lists a selection of classes was made. Then a new contact with the school leader was made, where the leader was asked to inform the teachers concerned by the study. In addition, each teacher got a letter with information about the study. The students got information about the study from their teachers and from the first page in the questionnaire.
The ambition was to have a researcher from the Working Life Institute present at the school when the students answered the questionnaire. The completed questionnaires were gathered by the teachers or the researcher and brought to the Working Life Institute where they were de-identified. After that the questionnaires were sent to the company "Tabell och Form AB" for scanning and a primary data preparation.

Ergonomists from the Working Life Institute visited all selected schools to perform an ergonomic evaluation, according to a structured checklist, of the student's computer workplaces and to do a short interview with the person responsible for the computers at the school.

Purpose:

The aim of the study was to describe range of computer usage in school and in spear time and the prevalence of difficulties, especially in the locomotive organs, among high school students. The aim was also to examine if there is a connection between computer time and physical difficulties.

Datainsamlingen genomfördes på gymnasieskolor i Stockholms, Södermanlands, Uppsala och Västmanlands län under hösten 2005.

Studien bestod av två delar:
1. Frågeformulär till eleverna.
2. Ergonomisk bedömning av skolans datorarbetsplatser och kort intervju med datoransvarig på skolan.

Ett informationsbrev skickades till skolledarna, där studiens upplägg och genomförande redovisades. Därefter kontaktades skolledarna per telefon och tillfrågades om skolan önskade medverka i studien. Om de valde att deltaga, ombads de skicka en förteckning på skolans samtliga klasser i ÅK2 till Arbetslivsinstitutet. Från dessa listor gjorde ett urval av klasser. En ny kontakt togs därefter med skolledaren, som då ombads att informera de lärare som skulle komma att bli berörda av studien. Varje lärare fick dessutom ett brev med information om studien. Eleverna fick information om studien via lärarna och första sidan på frågeformuläret.
Ambitionen var att en försöksledare från Arbetslivsinstitutet skulle vara närvarande på skolan när eleverna besvarade frågeformuläret.
De ifyllda frågeformulären samlades in av lärarna, alternativt av försöksledaren, och fördes till Arbetslivsinstitutet, där de avidentifierades. Därefter skickades de till företaget Tabell o Form AB för scanning och en primär databearbetning.

Ergonomer från Arbetslivsinstitutet besökte samtliga utvalda skolor för att göra en ergonomisk bedömning, enligt en strukturerad checklista, av elevernas datorarbetsplatser samt en kort intervju med datoransvarig på skolan.

Syfte:

Syftet med studien var att beskriva omfattningen av datorarbete i skolan och på fritiden och förekomsten av besvär, särskilt i rörelseorganen, bland gymnasieelever. Syftet var också att undersöka om samband föreligger mellan datortid och kroppsliga besvär.
Datorrelaterad muskuloskeletal ohälsa bland gymnasieelever 2005 - Enkät till elever
Keywords: ill health; ohälsa; physical activities; fysisk aktivitet; lighting; belysning; television viewing; tv-tittande; pain; smärta; back pain; ryggont; headaches; huvudvärk; sleep; sömn; teacher-student relationship; lärare-elevförhållande; educational environment; utbildningsmiljö; social environment; social miljö; computer literacy; datorkunskap; access to information and communications technology; tillgång till informations- och kommunikationsteknologi; secondary schools; sekundärskolor; working conditions; arbetsförhållanden; computers; datorer; height (physiology); längd; weight (physiology); vikt; Higher and further education; Gymnasial och högre utbildning; HEALTH; HÄLSA; General health and well-being; Allmän hälsa och välbefinnande; Working conditions; Arbetsförhållanden; Youth; Ungdomar; Medical and Health Sciences; Medicin och hälsovetenskap